A Dictionary of Hallucinations - Blom, Jan Dirk.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The Dictionary of Hallucinations is an alphabetical listing of issues pertaining to hallucinations and other misperceptions. They can be roughly divided into five categories: 1. Definitions of individual hallucinatory symptoms 2. Medical conditions and substances associated with the mediation of hallucinations 3. Definitions of the terms hallucination and illusion by important historical authors 4. Historical figures who are known to have experienced hallucinations 5. Miscellaneous issues. Each of the definitions of individual hallucinatory symptoms includes: a definition of the term its etymological origin the year of introduction (if known) a reference to the author or authors who introduced the term (if known) a description of the current use a brief explanation of the etiology and pathophysiology of the symptom at hand (if known) references to related terms references to the literature. Jan Dirk Blom, M.D., Ph.D., is a clinical psychiatrist, specializing in the field of psychotic disorders. He holds a Ph.D. from the Philosophy Department of the University of Leiden, on the deconstruction of the biomedical schizophrenia concept. He is currently involved in a collaborative project with the University of Utrecht, on model based and model free analyses of fMRI activation patterns obtained from individuals with verbal auditory hallucinations, and an experimental treatment method with fMRI-guided repetitive transcranial magnetic stimulation.
A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.
Keywords: Medicine; Neurosciences; Neurology; Psychiatry; Biomedicine; Neurosciences; Psychiatry; Neurology